2017
DOI: 10.1180/claymin.2017.052.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Alkali activation of natural clay using a Ca(OH)2/Na2CO3 alkaline mixture

Abstract: An experimental investigation was conducted on the alkali activation of a kaolinitic clay using an alkaline mixture composed of hydrated lime (Ca(OH)2) and sodium carbonate (Na2CO3) solution. The Ca(OH)2/Na2CO3 alkaline mixture was developed to overcome the high cost and chemical aggression associated with classical alkaline solutions. The mineralogical composition and microstructure of the alkaline mixture and alkali-activation products were studied using X-ray diffraction, attenuated total reflectance-Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In contrast, zeolite Na-P1, zeolite LTA, sodalite, and analcime result when the concentration of NaOH in the reaction mixture is lower than a molarity of 4 [24,29]. Different cost-effective binary alkaline systems of low causticity have also been developed for the alkali-activation of kaolinite [22,30]. Esaifan et al [22] reported the formation of a kaliophilite zeolite by reacting kaolinite with calcium hydroxide/potassium carbonate (Ca(OH) 2 /K 2 CO 3 ) as the alkaline activating mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, zeolite Na-P1, zeolite LTA, sodalite, and analcime result when the concentration of NaOH in the reaction mixture is lower than a molarity of 4 [24,29]. Different cost-effective binary alkaline systems of low causticity have also been developed for the alkali-activation of kaolinite [22,30]. Esaifan et al [22] reported the formation of a kaliophilite zeolite by reacting kaolinite with calcium hydroxide/potassium carbonate (Ca(OH) 2 /K 2 CO 3 ) as the alkaline activating mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Esaifan et al [22] reported the formation of a kaliophilite zeolite by reacting kaolinite with calcium hydroxide/potassium carbonate (Ca(OH) 2 /K 2 CO 3 ) as the alkaline activating mixture. Shaqour et al [30] also synthesized a cancrinite-type zeolite by activating kaolinite with a calcium hydroxide/sodium carbonate (Ca(OH) 2 /Na 2 CO 3 ) alkaline mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The most common clay material used for geopolymers is dehydroxylated kaolin, known as metakaolin (Duxson et al , 2007; Hounsi et al , 2013; Shaqour et al , 2017). Less frequently, 2:1 dioctaheral-layer silicates such as illite, smectite or even interstratified illite–smectite may be used for the production of these binders.…”
mentioning
confidence: 99%
“…10 Industrially, Na 2 CO 3 is mainly produced through the Solvay process which requires large amount of thermal energy and CaCO 3 calcination. 33 The produced Na 2 CO 3 can have several uses in the industry: (1) for flue gas CO 2 sequestration through the production of NaHCO 3 , 34,35 (2) as an alkali activator for cements, either directly or in the production of activators such as sodium silicates, 36,37 (3) in the production of precipitated calcium carbonate from brine for use as a cement admixture, 38 (4) to regenerate the necessary NaOH, 21,[39][40][41] and/or (5) sold for the manufacture of other commodities (e.g. glass).…”
Section: Additional Discussionmentioning
confidence: 99%